The Argentine ant, Iridomyrmex humilis Mayr, indigenous ants and other epigaeic invertebrates of the fynbos in relation to fire and vegetation age - De Kock, Anneke Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.